Determinants of the Job Search Method among Rural Youth: The Case of Vhembe District in South Africa - Dagume, Mbulaheni Albert (International Journal of Economics and Financial Issues, 2021)
The paper investigates the extent to which socio-demographic factors influence the job search methods used by unemployed youth when seeking jobs in South Africa. The study used cross-sectional data on a representative sample of youth in the Vhembe District of South Africa’s Limpopo Province. A structured questionnaire was administered on a face to face basis to collect data from the respondents. A multistage probability sampling procedure was used to select a total of five hundred and eighty respondents. A multinomial logistic regression model was used to investigate how socio-demographic characteristics impact on the methods used by unemployed youth in their job search. The results show that only education has a bearing on the employment search method adopted, by the youth. Those who had secondary school education and below were more likely to search for employment at worksites, seek assistance from friends and relatives, but less likely to respond to adverts in the media than their counterparts with tertiary education. The latter used the method of direct application. The study recommends that Human Resource experts and managers should build their recruitment and selection strategies around adverts in the media, seek assistance from friends and relatives and using worksites as recruitment areas. Keywords: Determinants, Job search methods, multinomial logistic regression, Unemployed Youth, Vhembe District, South Africa JEL Classifications: J64; J21; C41 DOI: https://doi.org/10.32479/ijefi.11702